2020
DOI: 10.1051/0004-6361/202039099
|View full text |Cite
|
Sign up to set email alerts
|

Impulsive coronal heating during the interaction of surface magnetic fields in the lower solar atmosphere

Abstract: Coronal plasma in the cores of solar active regions is impulsively heated to more than 5 MK. The nature and location of the magnetic energy source responsible for such impulsive heating is poorly understood. Using observations of seven active regions from the Solar Dynamics Observatory, we found that a majority of coronal loops hosting hot plasma have at least one footpoint rooted in regions of interacting mixed magnetic polarity at the solar surface. In cases when co-temporal observations from the Interface R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 57 publications
5
26
0
Order By: Relevance
“…The light curves from the two opposite ends of the loop, that is, from B1 and B3, show rising trends well before the propagating brightenings from B2 actually reached them. This suggests the following scenario: although the main reconnection takes place near the apparent loop apex, the footpoints become excited simultaneously, which is similar to the near-simultaneous footpoint brightenings observed in active region core loops (see Chitta et al 2020). It is also possible, however, that (undetected) fainter propagating brightenings from L16, page 3 of 8 B2 have excited the footpoints B1 and B3.…”
Section: Event 1: Bifurcation Scenariomentioning
confidence: 57%
See 2 more Smart Citations
“…The light curves from the two opposite ends of the loop, that is, from B1 and B3, show rising trends well before the propagating brightenings from B2 actually reached them. This suggests the following scenario: although the main reconnection takes place near the apparent loop apex, the footpoints become excited simultaneously, which is similar to the near-simultaneous footpoint brightenings observed in active region core loops (see Chitta et al 2020). It is also possible, however, that (undetected) fainter propagating brightenings from L16, page 3 of 8 B2 have excited the footpoints B1 and B3.…”
Section: Event 1: Bifurcation Scenariomentioning
confidence: 57%
“…Because they are nearly ubiquitous, these brightenings were initially thought to be potential candidates for coronal heating (Hudson 1991). However, further investigations indicate that significantly more (∼100 times) of these events would be required in order to account for the necessary energy budget (Aschwanden et al 2000b;Chitta et al 2021a). White boxes outline the locations of the six events studied here.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…For observed parameter values, the energy release is sufficient to heat the chromosphere and corona and can account for a range of observed dynamic effects. More recently, the model has been supported and extended by an analysis of reconnection at a 3D separator current sheet [67], as well as by numerical simulations [131] and observations of heating in the core of ARs in bright loops with flux cancellation at their footpoints [132].…”
Section: Modelling and Observations Of 3d Magnetic Reconnectionmentioning
confidence: 99%
“…Chen et al (2014) presented a model for the formation of coronal loops in an emerging AR, where the loop formation is triggered by an increase in the upward-directed Poynting flux at the loop footpoints as a result of the advection of the photospheric magnetic field. The relationship between impulsive coronal heating in ARs and magnetic field evolution at the solar sur-face was investigated by Chitta et al (2018) and Chitta et al (2020). They found that the energy released through interactions between the opposite magnetic polarities in the photosphere could be responsible for the coronal emission in the cores of ARs.…”
Section: Introductionmentioning
confidence: 99%